Avaliação clinicopatológica de pacientes portadores de tumores malignos de origem não epitelial em região de cabeça e pescoço no município de Fortaleza- Ce - Pacheco, Isabela Alves (2010)
Malignant tumors of non-epithelial origin are considered rare in the head and neck region and they can show great morbidity and mortality. The aim of this study was to investigate the cases of sarcomas and melanomas in the head and neck region over the period from 1999 to 2008, in specialized centers located in the Municipality of Fortaleza. The data were collected from the register books of surgery of the head and neck and patient reports at the evaluated centers. Fifty-four cases were observed, being 36 sarcomas and 18 melanomas. As per the evaluation of the sarcomas, we have observed that the most assailed individuals were men with brown skin, ranging from 20 to 59 years old, with median age of 39.7. The relation man/woman was 1.7:1. The most prevailing histological type was the rhabdomyosarcoma, and the most attacked areas were the face and the cervical region. And as per the melanomas, adult men were also prevailing, ranging from 20 to 59 years old, with median age of 54.6. It has also been verified equal assailment in the brown and white races, with 33.3% in each one. The relation man/woman was 1.25:1. The most prevailing histological type was the superficial spreading melanoma, and the face skin was the most frequent location. In the evaluation of the origin, there was similarity in both diseases, being approximately half the patients in the capital city, and half in the state´s hinterland. As concerning the monitoring, the greatest part of the sample came from patients alive without evidence of the disease from the last consultation, corresponding to 41.6% in sarcomas and 44.5% in melanomas. The variation of therapy has also been observed in both groups, being the most common types of treatments, the association of surgery, radiotherapy and chemotherapy and surgery and radiotherapy for sarcomas and surgery, followed by surgery and radiotherapy for melanomas. Although malignant tumors of non-epithelial origin are rare in the head and neck region, they can show great morbidity and mortality and it is necessary the better understanding of their clinicalpatological aspects, in order to establish better treatment and life quality to these patients.